Analysis of The Management of State-Owned Assets Using The Governance, Risk Management, and Compliance (GRMC) Approach and Soft Systems Methodology: A Case Study of The Secretariat General of The House of Representatives of The Republic of Indonesia - Okki Carolina Darmawan (Interdisciplinary Social Studies, 2026)
State Property Administration (BMN) is a crucial process in managing state assets to support accountability, transparency, and organizational decision-making. Despite various regulations, the Audit Board (BPK) findings reveal recurring BMN administration problems within the Secretariat General of the House of Representatives of the Republic of Indonesia, including unlabeled assets, missing assets, and disorganized updates of the Room Goods Inventory (DBR). This study aims to identify the root causes of suboptimal BMN administration and formulate implementable improvement recommendations. The research used a qualitative approach with case study methods and Governance, Risk Management, and Compliance (GRC) analysis frameworks integrated with Soft Systems Methodology (SSM). Data was obtained through documentation studies of audit reports, regulations, and internal documents, as well as semi-structured interviews with parties involved in BMN management. The results of the study show that the problems of BMN administration are systemic and are influenced by interrelated aspects of governance, risk management, and compliance. Key findings include suboptimal supervision and coordination between units, limited resources in the implementation of asset inventory and labeling, and suboptimal use of control mechanisms in the administration process. Based on the results of the analysis, the study recommends strengthening governance, improving internal control, developing BMN management competencies, optimizing information systems, and implementing risk management in a more structured manner to increase the effectiveness of BMN administration within the Secretariat General of the House of Representatives of the Republic of Indonesia.